Penyuluhan Pengaturan Diet pada Pasien Diabetes Mellitus di Puskesmas Tamalate - Kada, Maria Kurnyata Rante (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Diabetes Mellitus (DM) is a chronic disease with a rising incidence in Indonesia. One important effort in controlling diabetes is proper dietary management, yet many patients still do not understand the principles of a diabetes diet. This community service activity aims to improve patient knowledge about diet management through counseling at the Tamalate Community Health Center. The implementation method included material delivery, discussion, healthy menu simulations, and pre- and post-test evaluations. The activity was held on August 23, 2025, with 35 diabetes patients participating. The evaluation results showed an increase in participant knowledge after the counseling session, as well as a positive response to the method used. The daily menu simulation was considered very helpful in helping participants understand the implementation of a diabetes diet. It can be concluded that this counseling session effectively increased patient knowledge about diet management. Follow-up in the form of ongoing nutritional support is needed to support patient behavior changes in diabetes management.